Relationship of servicescape and customer satisfaction in upscale restaurant of five star hotel / Roney Roger Sining - Roney Roger Sining (2010)
The physical environment may be an important determinant of customer satisfaction and subsequent behavior when services are consumed primarily for hedonic purposes and customers spend moderate to long periods of time in the physical surroundings. An example of this phenomenon would be in an upscale restaurant setting. This study explored the domain of the physical environment in an upscale restaurant context to develop a servicescape scale. Relevant literature was reviewed on architecture, environmental psychology, psychology, operations management, and marketing, highlighting empirical and theoretical contributions. Conceptualization and operationalization of the servicescape dimensions is presented, and the procedures used in constructing and refining scale to assess servicescape in an upscale restaurant of five star hotel. Servicescape consists of the facility aesthetics, perceived quality, cleanliness and layout accessibility. Evidence of the scale’s reliability has been shown on the next chapter. The study attempted to build a conceptual model of how the servicescape influenced customers’ satisfaction. Pearson correlation was used to test the relationships among the hypothesized relationships. Results revealed that servicescape affected the level of satisfaction of customers. Finally, implications for restaurateurs and researchers were discussed.